2017
DOI: 10.2196/mhealth.7886
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Acceptance of Smartphone Health Technology for Chronic Disease Management: A Theoretical Model and Empirical Test

Abstract: BackgroundChronic disease patients often face multiple challenges from difficult comorbidities. Smartphone health technology can be used to help them manage their conditions only if they accept and use the technology.ObjectiveThe aim of this study was to develop and test a theoretical model to predict and explain the factors influencing patients’ acceptance of smartphone health technology for chronic disease management.MethodsMultiple theories and factors that may influence patients’ acceptance of smartphone h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
157
2
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(192 citation statements)
references
References 44 publications
23
157
2
4
Order By: Relevance
“…This is not consistent with previous research findings and the study by Hoque that gender was strongly associated with the adoption and use of mHealth in developing countries. 38,39 Venkatesh et al 31 suggested that age has received very little attention in the technology acceptance research literature, and this is consistent with the finding of this research. Zhao et al showed that different age groups have specific moderating effects on mHealth services adoption.…”
Section: Discussionsupporting
confidence: 87%
“…This is not consistent with previous research findings and the study by Hoque that gender was strongly associated with the adoption and use of mHealth in developing countries. 38,39 Venkatesh et al 31 suggested that age has received very little attention in the technology acceptance research literature, and this is consistent with the finding of this research. Zhao et al showed that different age groups have specific moderating effects on mHealth services adoption.…”
Section: Discussionsupporting
confidence: 87%
“…Some participants also noted that their own previous experience with poor health outcomes acted as facilitators by enabling them to recognize the importance of completing the questionnaire (reinforcement). Correspondingly, previous work has shown that perceived health threats predict patient intentions to use smartphone-based health technology [ 34 ]. This facilitator may be particularly relevant in diseases that are characterized by episodic flares, such as asthma [ 35 ], chronic obstructive pulmonary disease [ 36 ], and congestive heart failure [ 37 ] and can also be leveraged in patient-facing messaging to drive usage.…”
Section: Discussionmentioning
confidence: 94%
“…TAM has been widely used in studies of technology acceptance to predict users' intention to adopt a mobile health app (Dou et al, 2017;Sun et al, 2013). Sun et al (2013) formulated a model combining TAM theory with other models to explain consumers' acceptance of health technology (Sun et al, 2013); Hung and Jen also applied the TAM model to assess the students' intention to use mobile technology to manage their personal health (Hung and Jen, 2012).…”
Section: Perceived Ease Of Usementioning
confidence: 99%
“…Specially designed for the adoption of mobile health apps, it is believed that the intention of patients to use the app will depend greatly on the important others' suggestion, especially healthcare professionals as well as friends or relatives who recommend it to patients. The reason for the subjective norm on behavioral intention is that people will be more likely to adopt a particular behavior when the behavior is recommended by people who are important referents, even if the behaviors are not favored by the patients' belief structure, but patients are sufficiently motivated to conform to referees' perception if they think they need to adopt certain behaviours (Deng et al, 2014;Dou et al, 2017).…”
Section: Subjective Normmentioning
confidence: 99%
See 1 more Smart Citation